Layanan Bimbingan Klasikal Bidang Belajar untuk Meningkatkan Motivasi Berprestasi pada Siswa Underachiever Gifted - Rismayadi, Hendri; Suherman, Suherman; Yusuf, Syamsu (Psikopedagogia, 2017)
This study aimed to understand the effectiveness of the classroom guidance activity for the academic aspect to improve achievement motivation underachiever gifted students in SMA Negeri 4 Bandung. This was an experimental study with pre-experimental design. Â The data were collected through achievement motivation scale. The subject of this study was 30 students of class X SMA Negeri 4 Bandung. The sample was taken by using purposive sampling technique. The data analysis technique of this study was paired sample t-test statistical formula.Â  The result of this study showed that classroom guidance activity for the academic aspect was effective to improve achievement motivation underachiever gifted students. This study generates a new strategy in the form of classroom guidance activity for the academic aspect was effective to improve achievement motivation underachiever gifted students.